Evolução do rebanho holandês em uma propriedade do sudoeste paranaense - Oliveira, Oelyton Nunes de (2014)
The objective of this study was to evaluate milk production in dairy cows and average daily gain (ADG) of heifers in the rearing and weaning weight of calves in a property southwest of Paraná. The study was conducted on the property of Mr. Paulino Bartiniski Santa Cruz community in Cruzeiro do Iguaçu- PR during the years 2012 and 2013. The property has an area of 10 hectares. 13 heifers and 16 lactating animals, all Holstein were used. The animals were evaluated in four treatments (summer, autumn, winter, spring). For milk production, in 2012 and 2014, was different (P < 0.05 ) during winter, reaching 20.28 kg /animal/day in 2012 and 16.31 kg / animal / day in the year 2013, with 2012 production, 34.96, 21.40 and 27.76% higher compared to summer, fall and spring of the same year respectively. Significant effect occurred in spring and winter season, with an ADG of 0.683 and 0.535 kg/animal/day in spring and winter respectively, which were seasons where there was a higher gain, 47% higher compared to the summer and fall. There was no difference between treatments, evaluating the Holstein calves weaned at 60 days.